2012
DOI: 10.1007/s10750-011-0982-z
|View full text |Cite
|
Sign up to set email alerts
|

When season does not matter: summer and winter trophic ecology of Arctic amphipods

Abstract: Polar marine ecosystems' functioning is known to be strongly affected by the seasonality of water column production. However, a response of benthic organisms may range from close coupling to total decoupling from seasonal variability of environmental processes, depending on a feeding strategy. In this study, we used a multi-method approach (gut content, lipid and stable isotope analyses) to examine trophic ecology and major food sources of a large set of Arctic sub-littoral amphipods, and to evaluate whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 113 publications
(204 reference statements)
1
23
1
2
Order By: Relevance
“…Selection of POM particles is based on their size, quality, and composition, and some benthic consumers with high δ 13 C values may have selected for ice algal-derived POM. Based on the slow turnover time in Arctic benthic consumer tissues (McMahon et al, 2006;Kaufman et al, 2008;Weems et al, 2012) and the low benthic organism δ 13 C seasonal variability ( o1‰) recorded in previous Arctic studies (Dunton et al, 1989;Kedra et al, 2012;Legezynska et al, 2012;Søreide et al, 2013;Carroll et al, 2014) and in this study, isotopic enrichment from ice-algal ingestion should be measurable even months after the ice-algal deposition. Similar reliance of Arctic benthic communities on sea-ice diatoms through tight sympagic-benthic coupling has been reported for the Svalbard Archipelago (Søreide et al, 2013).…”
Section: Benthic Faunal Assimilation Pathwaysmentioning
confidence: 59%
“…Selection of POM particles is based on their size, quality, and composition, and some benthic consumers with high δ 13 C values may have selected for ice algal-derived POM. Based on the slow turnover time in Arctic benthic consumer tissues (McMahon et al, 2006;Kaufman et al, 2008;Weems et al, 2012) and the low benthic organism δ 13 C seasonal variability ( o1‰) recorded in previous Arctic studies (Dunton et al, 1989;Kedra et al, 2012;Legezynska et al, 2012;Søreide et al, 2013;Carroll et al, 2014) and in this study, isotopic enrichment from ice-algal ingestion should be measurable even months after the ice-algal deposition. Similar reliance of Arctic benthic communities on sea-ice diatoms through tight sympagic-benthic coupling has been reported for the Svalbard Archipelago (Søreide et al, 2013).…”
Section: Benthic Faunal Assimilation Pathwaysmentioning
confidence: 59%
“…As this caprellid is assumed to be a suspension feeder (Guerra-García 2002;Legeżyń ska et al 2012), some effect of sediment disturbance on the caprellid distribution in localities adjacent to glacier fronts was expected. In areas exposed to high sediment stress, suspension-feeding organisms suffer damage resulting from burial or clogging of the filtering apparatus (Moore 1977;Ronowicz et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In areas exposed to high sediment stress, suspension-feeding organisms suffer damage resulting from burial or clogging of the filtering apparatus (Moore 1977;Ronowicz et al 2011). However, recent studies of gut contents of C. septentrionalis (Legeżyń ska et al 2012) revealed the possibility of other means of feeding such as predation and scraping (Legeżyń ska et al 2012). Employment of different feeding strategies by C. septentrionalis may be the adaptation to survive in a sediment-impacted environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amphipod feeding preferences have been traditionally assessed using in situ and laboratory observations, feeding experiments, gut content analyses, and studies of the functional morphology of feeding appendages (Legeżyńska et al 2012). Knowledge of amphipod feeding ecology has recently expanded owing to the use of biomarkers, such as fatty acid biochemical profiles (Jaschinski et al 2011;McLeod et al 2013;Baeza-Rojano et al 2014) and stable nitrogen (δ 15 N) and carbon (δ 13 C) isotopes (Olabarria et al 2009;Mancinelli 2012;Jeong et al 2012).…”
Section: Introductionmentioning
confidence: 99%